Simulation of Distance Relay Operation on Fault Condition in MATLAB Software/Simulink - Abdullah Asuhaimi bin Mohd Zin; J. Tavalaei; Mohd Hafiz bin Habibuddin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In this paper a distance relay is simulated in theproposed transmission line protection which is combinationof overhead line and significant part of underground cable.Transmission line is modeled as distributed parameter insteadof lumped parameter to have more accurate analysis compareto conventional analysis. Voltage and current are sampled atrelay point. But, high charging current of cable affects distancerelay operation. Using appropriate filtering can reduce chargingcurrent effect on distance relay. Simulated impedance will becompared with positive sequence impedance of power system inorder to evaluate simulated relay. The relay shows a good resultfor faults in zone 1, but high resistance faults force distance relayto mis-operation.